"Improving Long-Term Psychiatric Care: Bring Back the Asylum": Implications for Ethnic Minority Individuals. Issue 1 (2nd January 2016) - Mfoafo-M'Carthy, Magnus
ABSTRACT: This article is a response to a previous article published in The Journal of the American Medical Association ( JAMA ) advocating for the reintroduction of the asylum system. Despite the arguments made by the authors, this author believes that reverting to the asylum system would not be beneficial for individuals with mental illness. This is due to the impact of the asylum system on a large number of this client population. Also, the reintroduction of the asylum system would worsen the plight of persons from ethnic minority backgrounds, based on the discriminatory practices of the health care system in the Western world.